PENDIDIKAN ISLAM DI SINGAPURA - M. Fidhul Akhyari; Tantohadi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
Islamic education is a process that takes place continuously and sustainably. Therefore, the task and function of Islamic education is the education of the whole person and lasts throughout life. This concept means that the tasks and functions of education are targeted at students who continue to develop dynamically, from the womb to the end of life. In short, the ultimate goal of Islamic education is to strive to create a perfect Muslim person, who can carry out his function as 'abid and caliph on earth. The aim of Islamic education is summarized in the ideals of every Muslim and Muslimat, namely to obtain happiness in this world and happiness in the afterlife.